Vaccine-Derived Polioviruses, Central African Republic, 2019 - (:unkn) unknown (My University, 2021)
Since May 2019, the Central African Republic has experienced a poliomyelitis outbreak caused by type 2 vaccine-derived polioviruses (VDPV-2s). The outbreak affected Bangui, the capital city, and 10 districts across the country. The outbreak resulted from several independent emergence events of VDPV-2s featuring recombinant genomes with complex mosaic genomes. The low number of mutations (<20) in the viral capsid protein 1-encoding region compared with the vaccine strain suggests that VDPV-2 had been circulating for a relatively short time (probably <3 years) before being isolated. Environmental surveillance, which relies on a limited number of sampling sites in the Central African Republic and does not cover the whole country, failed to detect the circulation of VDPV-2s before some had induced poliomyelitis in children.
Keywords: African Research